2015
DOI: 10.1371/journal.pone.0126973
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome and iTRAQ Proteome Analyses of Citrus Root Responses to Candidatus Liberibacter asiaticus Infection

Abstract: Root samples of ‘Sanhu’ red tangerine trees infected with and without Candidatus Liberibacter asiaticus (CLas) were collected at 50 days post inoculation and subjected to RNA-sequencing and isobaric tags for relative and absolute quantification (iTRAQ) to profile the differentially expressed genes (DEGs) and proteins (DEPs), respectively. Quantitative real-time PCR was subsequently used to confirm the expression of 16 selected DEGs. Results showed that a total of 3956 genes and 78 proteins were differentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
81
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(92 citation statements)
references
References 72 publications
7
81
2
2
Order By: Relevance
“…Many of these metabolites play a crucial role on plant metabolic processes. Several transcriptomic, proteomic and metabolomic studies revealed an important reprograming of citrus trees following CLas or CLam infection (Kim et al ., ; Aritua et al ., ; Mafra et al ., ; Nwugo et al ., ; Vyas et al ., ; Xu et al ., ; Zhong et al ., , ). These studies found changes in amino acids, sugars and other metabolites including bitter compounds such as limonin (Cevallos‐Cevallos et al ., ; Kim et al ., ; Baldwin et al ., ; Rosales & Burns, ; Slisz et al ., ; Chin et al ., ).…”
Section: The Effect Of Bacterial Pathogens On Plant Metabolism and Immentioning
confidence: 99%
“…Many of these metabolites play a crucial role on plant metabolic processes. Several transcriptomic, proteomic and metabolomic studies revealed an important reprograming of citrus trees following CLas or CLam infection (Kim et al ., ; Aritua et al ., ; Mafra et al ., ; Nwugo et al ., ; Vyas et al ., ; Xu et al ., ; Zhong et al ., , ). These studies found changes in amino acids, sugars and other metabolites including bitter compounds such as limonin (Cevallos‐Cevallos et al ., ; Kim et al ., ; Baldwin et al ., ; Rosales & Burns, ; Slisz et al ., ; Chin et al ., ).…”
Section: The Effect Of Bacterial Pathogens On Plant Metabolism and Immentioning
confidence: 99%
“…Zhong et al . () reported the carbohydrate metabolism and hormone synthesis signalling genes in roots are altered as early as 50 days post‐inoculation. However, an extensive analysis of carbohydrate status in relation to stress‐related gene expression at the early stage of Las infection of roots is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies at the genomic level have been ascertained that HLB can alter the expression of a large number of genes in various organs of infected plants (Kim et al, 2009;Liao and Burns, 2012;Mafra et al, 2013;Zheng and Zhao, 2013;Aritua et al, 2013;Zhong et al, 2015;Wang et al, 2016). Some genes are overexpressed, but others reduce its expression.…”
Section: Introductionmentioning
confidence: 99%
“…Some genes are overexpressed, but others reduce its expression. Genes whose expression is altered are mainly related to the plant's defense systems (Kim et al, 2009;Rawat et al, 2015;Wang et al, 2016), the sucrose and starch metabolism (Xu et al, 2015;Rawat et al, 2015;Wang et al, 2016), synthesis and signaling hormones (Martinelli et al, 2012), nutrients absorption and transport (Zhang et al, 2015;Rawat et al, 2015;Zhong et al, 2015). Mafra et al, 2013;Zheng y Zhao, 2013;Aritua et al, 2013;Zhong et al, 2015;Wang, et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation